1977
DOI: 10.1177/009127007701700409
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Diuretic Therapy with Metolazone of Renal Failure and the Nephrotic Syndrome

Abstract: The effects of the new diuretic metolazone were studied in ten patients with chronic renal insufficiency and ten with nephrotic syndrome. Patients were maintained on metolazone for up to 44 months. Beneficial effects of treatment included loss of edema and improved control of blood pressure. The natriuretic effect of metolazone facilitated the use of sodium bicarbonate to treat acidosis in several patients. Concurrent administration of metolazone and furosemide produced a dramatic diuresis in one patient resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Hence, potentially 67% (normo/euvolemic) of NS patients can be treated with diuretics alone. However, the published literature on diuretics alone in severe edema is mostly limited to reports of its use in patients (usually adults) with chronic edema and obvious signs of volume overload as in GN and chronic renal failure (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, potentially 67% (normo/euvolemic) of NS patients can be treated with diuretics alone. However, the published literature on diuretics alone in severe edema is mostly limited to reports of its use in patients (usually adults) with chronic edema and obvious signs of volume overload as in GN and chronic renal failure (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, сама по себе реабсорбция натрия в дистальных канальцах про-исходит в меньших объемах, чем в восходящей ча-сти петли Генле [82]. Метолазон, производное хи-нетазона, является исключением среди тиазидных диуретиков, так как он сохраняет эффективность при почечной недостаточности или диуретик-резистентных состояниях [83]. Однако действие ограничивается его медленной и непредсказуемой абсорбцией.…”
Section: огляд / Reviewunclassified
“…As detailed in Table 1, these early studies included 5 small heterogeneous trials of metolazone in CKD all with a before-and-after design [22][23][24][25][26], and in general GFR was low with 2 trials reporting creatinine clearances for individual subjects as low as 1 mL/min. These studies showed an improvement in reported diuretic or antihypertensive outcomes with metolazone administration, and these early positive results are likely the reason that there is a persistent belief that metolazone is the unique thiazide that is effective in advanced CKD [27].…”
Section: Older Studies Of Thiazides In Ckdmentioning
confidence: 99%